Comparative performance of PPPs and traditional procurement projects in Indonesia. Issue 2 (6th March 2017) - Atmo, Gigih Udi; Duffield, Colin; Zhang, Lihai; Wilson, David Ian
Abstract : Purpose: The purpose of this paper is to investigate the outcomes of Indonesian power projects as representative projects of Asian emerging economies that were procured via public-private partnerships (PPPs) and traditional public sector procurement. Power generation infrastructure delivery in emerging economies frequently seeks private participation via PPPs as one of the key mechanisms to attract private finance. Undertaking a comparative benchmark study of the outcomes of Indonesian power projects provides an opportunity to explore the historic evidence as to whether PPPs deliver better outcomes than traditional public procurement in emerging economies. Design/methodology/approach: This paper reports on a study of the performance of 56 Indonesian power projects procured via either PPPs or traditional procurement. First, it focusses on project time and cost outcomes of power plant facility during construction and commissioning and then extends this comparison to consider the operating availability of power plants during their first two years of operation. Findings: The results indicate that PPP projects had superior time and operating availability to those procured traditionally whereas no significant differences were identified in the cost performance between PPPs and traditionally procured projects. These findings highlight the importance of adopting policies that are supported by broader sources of international financiers and high quality power plant developers. Research limitations/implications: The quality performance analyses of projects (based on equivalent available factor indices) were limited to the power plants in the Java-Bali region where the majority of projects are large scale power plants. Practical implications: This study provides an empirical basis for governments of emerging economies to select the most beneficial procurement strategy for power plant projects. It highlights the importance of selecting experienced providers and to adopt policies that attract high quality international project financiers and power plant developers. This includes the need to ensure the commercial viability of projects and to seriously consider the use of cleaner power technologies. Originality/value: This study is the first to compare the outcomes of power projects in Asian emerging economies delivered via PPPs against those delivered by traditional public procurement that includes consideration of the quality of the delivered product.